Cultural bridges in film: evolving perspectives of transnational cinema - Al-Maliki, Mona Shaddad Siraj (Frontiers in Communication, 2025)
The emergence of transnational cinema as a dynamic force in modern filmmaking has resulted in the promotion of cultural interaction and the formation of global narrative trends. This systematic study, which is driven by the PRISMA framework, is a synthesis of contemporary scholarly viewpoints on how transnational cinema acts as a cultural bridge. The purpose of this study is to synthesize the findings from a carefully selected sample of fifteen research papers, with special emphasis placed on stringent inclusion–exclusion criteria and the utilization of the PRISMA methodology. The sample of articles utilized in this study spans the years 2006 to 2023. The review sheds light on a variety of influences that have influenced the shifting viewpoints on transnational cinema. The practice of transnational cinema encourages cultural hybridity while simultaneously challenging established national identities. One of the most important factors in growing the worldwide effect of films is the role that co-productions and digital platforms play. According to the findings, transnational cinema is facilitating a transformation in the manner in which cultural identities are shown and understood. The blending of different film techniques and the telling of stories from other cultures contributes to the enrichment of global cinema and defies the rigid definitions of national industry. Several topics, including hybridity, diasporic identity, cross-border cooperation, and worldwide audience reception, are investigated in this research. Through an examination of several studies, this study sheds light on the primary tendencies and debates that are characteristic of the modern international cinematic discourse. In further investigations, the phenomena of the digital revolution and the impact it has had on the process of reframing global narratives need to be the primary focus.